MEDIA PEMBELAJARAN SISTEM STARTER DI PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF - Andi Supriyanto; Tri Kuat; Edhy Susatya (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
This research is motivated by the low learning outcomes of students in the subject of Light Vehicle Electrical Maintenance, where 17 out of 20 students in grade XI obtained scores below the minimum completion criteria due to conventional learning dominated by lecture methods. The focus of this research problem is directed at the development and testing of the feasibility of learning media in the form of a starter system stand containing interactive electrical diagrams for students of the Automotive Light Vehicle Engineering Expertise Program at SMK Muhammadiyah Wanareja. The research strategy implemented adopts the Research and Development (R&D) method by implementing the ADDIE development model which includes the stages of analysis, design, development, implementation, and product evaluation. Data collection was carried out through initial observations, filling out expert validation questionnaires, and assessment response sheets from students as respondents. The research findings show that the validation results from the media expert component obtained a classification score of no revision, while the assessment from the material expert aspect fell into the qualification of sufficient. The main conclusion of the study confirms that the use of this starter system demonstration stand has proven effective in significantly improving technical competence, motor activity, and understanding of automotive electrical material for students in field trials with the final result being categorized as no revision. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa pada mata pelajaran Pemeliharaan Kelistrikan Kendaraan Ringan, di mana 17 dari 20 siswa kelas XI memperoleh nilai di bawah kriteria ketuntasan minimum akibat pembelajaran konvensional yang didominasi metode ceramah. Fokus masalah riset ini diarahkan pada pengembangan dan pengujian kelayakan media pembelajaran berbentuk stand sistem starter yang memuat diagram kelistrikan interaktif bagi siswa Program Keahlian Teknik Kendaraan Ringan Otomotif di SMK Muhammadiyah Wanareja. Strategi penelitian yang diterapkan mengadopsi metode Research and Development (R&D) dengan menerapkan model pengembangan ADDIE yang meliputi tahapan analisis, desain, pengembangan, implementasi, hingga evaluasi produk. Pengumpulan data dilakukan melalui observasi awal, pengisian angket validasi ahli, serta lembar respon penilaian dari peserta didik selaku responden. Temuan riset menunjukkan bahwa hasil validasi dari komponen ahli media mendapatkan skor klasifikasi tidak revisi, sementara penilaian dari aspek ahli materi masuk ke dalam kualifikasi cukup layak. Simpulan utama penelitian menegaskan bahwa penggunaan stand alat peraga sistem starter ini terbukti efektif meningkatkan kompetensi teknis, aktivitas motorik, serta pemahaman materi kelistrikan otomotif siswa secara signifikan pada uji coba lapangan dengan hasil akhir berkategori tidak revisi.